The two novel DLL4-targeting antibody-drug conjugates MvM03 and MGD03 show potent anti-tumour activity in breast cancer xenograft models. (28th November 2017) - Wang, Shijing; Zhou, Rihong; Sun, Fumou; Li, Renjie; Wang, Min; Wu, Min
Abstract: The anti-human Delta-like 4 (DLL4) monoclonal antibody MMGZ01 has a high affinity to hrDLL4 and arrests the DLL4-mediated human umbilical vein endothelial cell (HUVEC) phenotype, promotes immature vessels, and effectively reduces breast cancer cell growth in vivo. To develop a much more effective therapy, we conjugated MMGZ01 with two small-molecule cytotoxic agents, i.e., monomethyl auristatin E (MMAE) and doxorubicin (DOX), with different linkers to generate antibody–drug conjugates (ADCs), i.e., MMGZ01-vc-MMAE (named MvM03) and MMGZ01-GMBS-DOX (named MGD03), that are more potent therapeutic agents than naked antibody therapeutic agents. The produced anti-DLL4 ADCs can be effectively directed against DLL4 and internalized. Then, the release of MMAE or DOX into the cytosol can induce G2/M or G0/G1 phase growth arrest and cell death through the induction of apoptosis. In vitro, MvM03 was highly potent and selective against DLL4 cell lines. The anti-DLL4 ADCs, particularly MvM03, showed more potent anti-tumour activity than Docetaxel, which is an inhibitor of the depolymerisation of microtubules, in two xenograft breast cancer tumour models. Our findings indicate that anti-DLL4 ADCs have promising potential as an effective therapy for breast cancer. Highlights: A novel anti-DLL4 monoclonal antibody MMGZ01 couples with two drugs, i.e. MMAE and DOX to develop two novel ADCs. The two anti-DLL4 ADCs help improve targeting activity and reduce toxicity of MMAE and DOX. The anti-DLL4 ADCs have superior anti-tumour activities in vivo.